A comparison of clinical outcomes in PPMS in the INFORMS original trial data set. (October 2021) - Koch, Marcus W; Mostert, Jop P; Uitdehaag, Bernard; Cutter, Gary
Background: The expanded disability status scale (EDSS) is the standard clinical outcome measure in primary progressive multiple sclerosis (PPMS), even though the timed 25-foot walk (T25FW), nine-hole peg test (NHPT) or combinations of these measures may be more useful. The paced auditory serial addition test (PASAT) is a widely used cognitive measure in MS, but little is known about change in PASAT scores over time in PPMS. Objective: The objective of this study is to compare clinical outcome measures in a large PPMS trial data set. Methods: We determined significant worsening events on the EDSS, T25FW and NHPT, and PASAT scores over the course of this 3-year trial. We compared unconfirmed, confirmed and sustained disability worsening and contrasted disability worsening with similarly defined improvement. We examined the association of baseline characteristics with the risk of disability worsening at 12, 24 and 36 months with logistic regression models. Results: The EDSS and T25FW showed most worsening events, while only few patients worsened on the NHPT. Adding the NHPT to a combined outcome added only few further worsening events. PASAT scores slightly increased over time, possibly due to a practice effect. Conclusion: Both the EDSS and T25FW, but not NHPT or PASAT, appear to be useful outcome measures in PPMS.